Prospective Evaluation of Laparoscopic Sacrocolpopexy with Concomitant Laparoscopic-Assisted Total Vaginal Hysterectomy - Ivo Faehnle-Schiegg; Janine Abgottspon; Janine Frey; Joerg Krebs; Corina Christmann-Schmid (Surgeries, 2022)
(1) Background: Sacrocolpopexy (SCP) with subtotal hysterectomy (SH) is a standard procedure for the treatment of utero-vaginal prolapse. Several disadvantages are associated with the remaining cervix; therefor, SCP with total hysterectomy (TH) may be preferred. According to some publications, SCP with concomitant TH is associated with higher rates of mesh extrusion. Our hypothesis is that mesh extrusion at the apex can be avoided through prevention of thermal injury and through vaginal cuff suturing when performing the laparoscopic sacrocolpopexy combined with a laparoscopic-assisted vaginal total hysterectomy (LAVH). (2) Methods: This prospective cohort study was performed from 2016 until January 2019 including women with a utero-vaginal prolapse undergoing laparoscopic SCP with LAVH. The SCP was performed utilizing a non-absorbable polypropylene macroporous mesh (EndoGYNious®). The primary outcome was the mesh extrusion rate after SCP with concomitant LAVH. The secondary outcome was the objective and functional outcome. (3) There were 50 women included in this prospective cohort. At follow up of 6–12 weeks postoperatively, no mesh extrusion was detected and objectified. Overall, all women showed excellent anatomical and functional outcome. The median time from surgery was 42 months. (4) Laparoscopic SCP with concomitant LAVH showed no increased risk of mesh extrusion and good objective and functional outcomes.